A Rare Case of Todani Type-III Choledochal Cyst - Lourenço,Ana Luísa (2020)
Abstract Choledochal cysts constitute a group of rare biliary tree disorders, which are divided in several subtypes according to Todani classification. Type III choledochal cyst is one of the rarest subtype. Symptoms are almost always associated with complications such as cholangitis or pancreatitis, usually due to biliary stasis, choledocholithiasis, recurrent infection or inflammatory events. This article describes a case of a patient who presented to the emergency department due to fever and abdominal pain, owing to Todani type III cystic obstruction with representative findings in the computed tomography study and endoscopic confirmation.